Identifying research gaps in supply chain innovation - Fatemeh Seidiaghilabadi; Zahra Seidiaghilabadi; Aida Miralmasi (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: In recent years, supply chain innovation (SCI) has become a central characteristic of firms in creating dynamic competitive advantages. The present study aims to examine the SCI literature in the last five years. Originality: Although there is much research on supply chain management (SCM), innovations, sustainable supply chain (SSC), and green supply chain (GSC), limited research has identified gaps in the SCI. Findings: The study offers useful implications for researchers, managers, marketers, and other stakeholders involved in the SCI. The study also motivates the researchers to conduct additional studies in the area of SCI. Furthermore, the results of this study contribute to building new research agendas concerning SCI. Methodology: The study adopts a qualitative content analysis approach to examine the literature on SCI (from 2014 to 2019). Qualitative software MAXQDA12 was applied for literature content' classification and coding.
urn:nbn:de:gbv:830-882.054287; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 650; Supply chain innovation; Qualitative content analysis; MAXQDA